COMPENSATION STRATEGIES FOR VOCABULARY LIMITATIONS IN BIPA LEARNING: A CASE STUDY OF VIETNAMESE LEARNERS - Nila Agustin Prianti; Muhammad Isnaini; Arif Setiawan; Nguyen Thi Thu Hang (Curricula: Journal of Teaching and Learning, 2025)
In the context of learning Indonesian as a foreign language, limited vocabulary often becomes one of the main obstacles that hinder learners from communicating effectively. To overcome this limitation, learners frequently employ various communication strategies that allow them to maintain interaction despite gaps in linguistic competence. Understanding how these strategies are used is essential for improving the effectiveness of Indonesian language teaching for foreign learners (BIPA). This study aims to identify and analyze the compensation strategies employed by BIPA learners in Vietnam when dealing with limitations in Indonesian vocabulary during classroom interactions. This research employed a qualitative descriptive approach. The study was conducted at Ho Chi Minh City Open University, Vietnam, involving Vietnamese students enrolled in an Indonesian language class. Data were collected through classroom observation, semi-structured interviews, and documentation of learners’ utterances during learning activities. A total of 20 instances of learner utterances and communicative behaviors indicating the use of compensation strategies were identified and analyzed. Data analysis followed the qualitative analysis model of data reduction, data display, and conclusion drawing. The findings reveal that BIPA learners employ several types of compensation strategies to maintain communication. These strategies include code-switching, lexical borrowing, lexical approximation, circumlocution, and gestural strategies. Among these strategies, lexical borrowing from English was found to be the most frequently used, indicating the role of English as a linguistic support in communication. Nonverbal strategies such as gestures were also commonly used to clarify meanings when learners lacked appropriate vocabulary. The study suggests that compensation strategies play an important role in sustaining communication and supporting the development of learners’ communicative competence. Therefore, BIPA instruction should adopt communicative and contextual approaches that allow learners to utilize such strategies while gradually expanding their vocabulary repertoire.